Answer:
B
Step-by-step explanation:
In The rest of the problems, you add or subtract first.
Answer:
x = 2
y = 0
Step-by-step explanation:
We can solve using substitution, substitute y in the first equation with the second equation:
-(-6x + 12) + 3x = 6
Distribute the negative sign:
6x - 12 + 3x = 6
Combine like terms:
9x - 12 = 6
Isolate the variable and solve for x by adding 12 in both sides:
9x = 18
x = 2
Substitute 2 with x in any equation to find the value of y:
-y + 3(2) = 6
-y + 6 = 6
Subtract 6 in both sides to isolate the variable:
-y = 0
0/-1 = 0
y = 0
Our answer would be x = 2 and y = 0